Behaviour of expansive clay beds with fly-ash-stabilised clay cushion. Issue 1 (6th February 2022) - Phanikumar, B. R.
Abstract : Stabilisation of expansive soils with various additives such as lime and fly ash has been shown to be a viable technique to counteract heave and shrinkage. This paper presents experimental results obtained from tests performed on expansive clay beds with fly-ash-stabilised clay cushions of varying thicknesses and fly-ash content. The amount and rate of heave, swelling pressure and stress–settlement characteristics of the expansive clay beds were studied. The results indicated that when fly-ash-stabilised clay cushions were provided over expansive clay beds, heave and swelling pressure decreased in comparison with the heave and swelling pressure of untreated expansive clay beds but, heave and swelling pressure increased with increasing fly-ash content for a given thickness of the cushion. For a given fly-ash content, however, heave and swelling pressure decreased with increasing thickness. Heave reduced by 70% when a 75 mm thick clay cushion stabilised with 10% fly-ash content was used. The stress–settlement characteristics of the expansive clay beds with a fly-ash-stabilised clay cushion improved. The settlement of the footing on a 50 mm thick clay cushion decreased by about 43% when the fly-ash content was increased from 0 to 10%.